2017
DOI: 10.5430/jnep.v7n6p100
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students' knowledge and attitude regarding pain management of children in Upper Egypt

Abstract: Pain assessment and management require nurses to be equipped with adequate knowledge and proper attitudes. This research aimed to assess undergraduate nursing students' knowledge and attitude regarding pain management in children. Descriptive cross-sectional research design was utilized. This work was implemented at Faculty of Nursing in Assiut University. The study subjects consisted of convenient sample of undergraduate nursing students at third and fourth year during the academic year 2015-2016. One tool wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 16 publications
10
35
0
Order By: Relevance
“…This study has shown that most nursing students reported themselves as having a good level of knowledge of pediatric pain and its management; however, their mean total correct score on the PNKAS was low, at 32.1%. This result is consistent with scores reported in previous studies (Al-Khawaldeh et al, 2013;Al Omari, 2016;Chiang et al, 2006;Chow and Chan, 2015;Gadallah et al, 2017;Khalaileh and Qadire, 2013;Ortiz et al, 2015;Rahimi-Madiseh et al, 2010). Table 3: Top 10 questions answered incorrectly by nursing students (frequency and percentage distribution) (Manworren, 2001) Items Answer N % 39B: "Your assessment, above, is made 2 hours after he received morphine 2 mg IV.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study has shown that most nursing students reported themselves as having a good level of knowledge of pediatric pain and its management; however, their mean total correct score on the PNKAS was low, at 32.1%. This result is consistent with scores reported in previous studies (Al-Khawaldeh et al, 2013;Al Omari, 2016;Chiang et al, 2006;Chow and Chan, 2015;Gadallah et al, 2017;Khalaileh and Qadire, 2013;Ortiz et al, 2015;Rahimi-Madiseh et al, 2010). Table 3: Top 10 questions answered incorrectly by nursing students (frequency and percentage distribution) (Manworren, 2001) Items Answer N % 39B: "Your assessment, above, is made 2 hours after he received morphine 2 mg IV.…”
Section: Discussionsupporting
confidence: 88%
“…Nursing students under 30 years of age scored higher than those whose age was 30 years or older, similar to the findings of Ekim and Ocakcı (2013). However, other studies have found no significant age-based difference in nursing students' knowledge and attitudes (Al-Khawaldeh et al, 2013;Gadallah et al, 2017). The above differences may be due to differences in setting, sampling method and size, and subjects' characteristics.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Emphasis should be placed on prelicensure nursing curriculum and educational provision across all levels and degrees to ensure that paediatric pain is clearly prominent within undergraduate/prelicensure nursing studies and preparation and that there is an access to the basic knowledge, skills and fundamental needs for effective pain management prior to clinical practice and caring for children in pain (Gadallah et al. ; Mackintosh‐Franklin ).…”
Section: Implications For Nursing and Health Policymentioning
confidence: 99%